Pengembangan Desain Antarmuka Pengguna e-Learning Pemrograman menggunakan Metode Rekayasa Kansei - Kharis Alfian; Retno Indah Rokhmawati; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
E-Learning technology has been widely used to support learning by various organizations and educational institutions, one of which is in learning programming. As one of the components of e-Learning technology, the user interface has an important role as the main means of accessing interaction between the system and the learner that can affect motivation, learning outcomes, and emotional conditions. In addition, it is known that many e-Learning products have been developed with more advanced technology, but pay less attention to the emotional aspects in their development so that they are not able to meet the tastes of learners and have an impact on comfort, age of use, and the success of learning objectives. Because of this background, research was conducted to find an overview of the programming user interface of e-Learning in accordance with the concept of the learner's emotions using the Kansei Engineering method so that the developed e-Learning interface can meet tastes, extend the life of e-Learning usage, and be able to provide user comfort in the process learn programming. Based on the test results, it is known that the interface developed using Kansei Engineering is able to provide comfort and convenience according to the concept of the learner's emotions as evidenced by user feedback and also usability testing on aspects of effectiveness of 93.125%, efficiency of 0.3 goals/second, and aspects of satisfaction using a questionnaire. System Usability Scale with a score of 76 which means good and acceptable.